Anticancer activity and cell cycle arrest evoked by ethanolic extract of cyperus rotundus in kb oral cancer cell lines - N.V.DHANYA; S.SELVI (International Journal of Pharma and Bio Sciences, 2017)
The present study was carried out to investigate the in vitro anticancer potential of ethanol extract of the rhizome of Cyperus rotundus in KB oral cancer cell lines. The anti-proliferative effect of Cyperus rotundus was assessed by MTT assay, SRB assay and LDH assay. The results of MTT and SRB assay showed significant cell death on dose dependent manner with an LD50 values at a concentration of 12.5μg/ml. Increased LDH leakage was an indicator of loss of membrane integrity. Acridine Orange/Ethidium Bromide (AO/EB) fluorescent staining confirmed apoptotic/dead cells in extract treated group. Flow cytometry analysis of cell cycle confirmed, significant increase in S phase attributing to S phase arrest of KB oral cancer cells. All these results establish the effect of Cyperus rotuondus as a potent anticancer agent against oral cancer cell lines.